2005
DOI: 10.4049/jimmunol.174.12.8027
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Chemokine Receptor CCR5 Promotes Murine Fulminant Liver Failure by Preventing the Apoptosis of Activated CD1d-Restricted NKT Cells

Abstract: Fulminant liver failure (FLF) consists of a cascade of events beginning with a presumed uncontrolled systemic activation of the immune system. The etiology of FLF remains undefined. In this study, we demonstrate that CCR5 deficiency promotes the development of acute FLF in mice following Con A administration by preventing activated hepatic CD1d-restricted NKT cells (but not conventional T cells) from dying from activation-induced apoptosis. The resistance of CCR5-deficient NKT cells from activation-induced apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
102
3
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(116 citation statements)
references
References 54 publications
10
102
3
1
Order By: Relevance
“…The depletion of NKT cells during liver fibrosis progression has been observed previously (12) and could be related to either activation-induced NKT cell death or loss of cell markers such as NK1.1 (38,41,42). In the CCl 4 fibrosis model, NKT cell apoptosis in particular was found to account for reduced NKT cell numbers in chronic injury (12), and it had been speculated that the depletion of NKT cells abrogated their beneficial effects on stellate cells.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The depletion of NKT cells during liver fibrosis progression has been observed previously (12) and could be related to either activation-induced NKT cell death or loss of cell markers such as NK1.1 (38,41,42). In the CCl 4 fibrosis model, NKT cell apoptosis in particular was found to account for reduced NKT cell numbers in chronic injury (12), and it had been speculated that the depletion of NKT cells abrogated their beneficial effects on stellate cells.…”
Section: Discussionmentioning
confidence: 96%
“…Their role in the pathogenesis of chronic liver injury and fibrosis is controversial. Experimental studies using Con A or a-GalCer demonstrated that NKT cell activation contributes to acute hepatitis (15,16,38), likely by releasing various proinflammatory cytokines and via Fas-mediated cell lysis (4). In HBVtransgenic mice, NKT cell activation promoted fibrosis progres- sion by secreting HSC-activating cytokines IL-4 and IL-13 (39), similar to observations from patients with chronic hepatitis B (40) and consistent with the cytokine expression pattern we identified in hepatic NKT cells isolated from murine injury models in WT, but not Cxcr6 2/2 mice.…”
Section: Discussionmentioning
confidence: 99%
“…6C. Although NKT cells rapidly disappeared after ConA stimulation for activation-induced cell death, 14,18 cytokines secreted by NKT cells might exert a function (Fig. 6C).…”
Section: Help Function Of Nkt Cells In Nk Cell-mediatedmentioning
confidence: 99%
“…For example activation of chemokine receptors promotes apoptosis in neurons and T cells as well as survival of glioblastoma, ovarian carcinoma, pancreatic adenocarcinoma and other cancer cells. [10][11][12] These previous data linking some chemokine receptors with apoptosis and the correlation between functional activation of CXCR4 and CCR7 and an invasive, metastatic phenotype of breast cancer cells together with the ability of these receptors to induce cytoskeletal changes have led us to hypothesize that CXCR4 and CCR7 may influence cancer cell metastasis by regulating detachment-induced apoptosis. We describe here a novel common role for CXCR4 and CCR7 in inhibiting anoikis, specifically in metastatic breast cancer cells.…”
mentioning
confidence: 99%